2019
DOI: 10.1111/caim.12346
|View full text |Cite
|
Sign up to set email alerts
|

Is overparenting harmful to creativity?

Abstract: Heavy parental involvement is widely believed to inhibit creativity. On the basis of this rationale and the self‐creativity literature, this study collected paired data to examine the effects of overparenting (which includes the parental arrangement of daily life affairs and parental involvement in schooling), team learning, and coaching by immediate supervisors on employee creativity (i.e., the creativity of Chinese only‐child millennial employees). The findings are described as follows. First, parental invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…The research results showed that from a psychological perspective, the most important variables included risk tolerance, entrepreneurial alertness, and confidence in skills, and education and past experience also played a key role in human capital. Khurosani (2018) and Zheng et al (2020) used structural equation modeling to conduct organizational learning culture research on managers and employees of the creative industry in Banten, Indonesia. The research results showed that transformation leaders had a positive impact on organizational learning culture but did not affect the creativity and organizational innovation of employees; organizational learning culture had a positive impact on employee creativity; employee creativity had a positive impact on organizational innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research results showed that from a psychological perspective, the most important variables included risk tolerance, entrepreneurial alertness, and confidence in skills, and education and past experience also played a key role in human capital. Khurosani (2018) and Zheng et al (2020) used structural equation modeling to conduct organizational learning culture research on managers and employees of the creative industry in Banten, Indonesia. The research results showed that transformation leaders had a positive impact on organizational learning culture but did not affect the creativity and organizational innovation of employees; organizational learning culture had a positive impact on employee creativity; employee creativity had a positive impact on organizational innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Communication plays an important role in forming a good contract. When new employees are employed, they should first feel that the enterprise is a big family, which requires honest and in-depth communication between managers and employees ( Chen, 2019 ; Zheng et al, 2020 ). Through effective communication, managers can understand employees’ inner needs and motivate some employees’ needs.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, this belief cannot represent the fair value of the market, but it will affect investors' decision-making and market behavior activities. From a behavioral finance perspective, investors with heterogeneous beliefs and preferences are often irrational (Zheng et al, 2020). In their decision-making and investment process, psychological factors play a very important role.…”
Section: Discussionmentioning
confidence: 99%